Analysis of RIM Expression and Function at Mouse Photoreceptor Ribbon Synapses - Löhner, Martina; Babai, Norbert; Müller, Tanja; Gierke, Kaspar; Atorf, Jenny; Joachimsthaler, Anneka; Peukert, Angela; Martens, Henrik; Feigenspan, Andreas; Kremers, Jan; Schoch, Susanne; Brandstätter, Johann Helmut; et al. (The Journal of Neuroscience, 2017)
RAB3A-interacting molecule (RIM) proteins are important regulators of transmitter release from active zones. At conventional chemical synapses, RIMs contribute substantially to vesicle priming and docking and their loss reduces the readily releasable pool of synaptic vesicles by up to 75%. The priming function of RIMs is mediated via the formation of a tripartite complex with Munc13 and RAB3A, which brings synaptic vesicles in close proximity to Ca(2+) channels and the fusion site and activates Munc13. We reported previously that, at mouse photoreceptor ribbon synapses, vesicle priming is Munc13 independent. In this study, we examined RIM expression, distribution, and function at male and female mouse photoreceptor ribbon synapses. We provide evidence that RIM1? and RIM1? are highly likely absent from mouse photoreceptors and that RIM2? is the major large RIM isoform present at photoreceptor ribbon synapses. We show that mouse photoreceptors predominantly express RIM2 variants that lack the interaction domain for Munc13. Loss of full-length RIM2? in a RIM2? mutant mouse only marginally perturbs photoreceptor synaptic transmission. Our findings therefore strongly argue for a priming mechanism at the photoreceptor ribbon synapse that is independent of the formation of a RIM-Munc13-RAB3A complex and thus provide further evidence for a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses in synaptic vesicle exocytosis.SIGNIFICANCE STATEMENT RAB3A-interacting molecules 1 and 2 (RIM1/2) are essential regulators of exocytosis. At conventional chemical synapses, their function involves Ca(2+) channel clustering and synaptic vesicle priming and docking through interactions with Munc13 and RAB3A, respectively. Examining wild-type and RIM2 mutant mice, we show here that the sensory photoreceptor ribbon synapses most likely lack RIM1 and predominantly express RIM2 variants that lack the interaction domain for Munc13. Our findings demonstrate that the photoreceptor-specific RIM variants are not essential for synaptic vesicle priming at photoreceptor ribbon synapses, which represents a fundamental difference between photoreceptor ribbon synapses and conventional chemical synapses with respect to synaptic vesicle priming mechanisms.
EVALuna2:21339

Identification and immunocytochemical characterization of Piccolino, a novel Piccolo splice variant selectively expressed at sensory ribbon synapses of the eye and ear - Regus-Leidig, Hanna; Ott, Corinna; Löhner, Martina; Atorf, Jenny; Fuchs, Michaela; Sedmak, Tina; Kremers, Jan; Fejtova, Anna; Gundelfinger, Eckart D.; Brandstätter, Johann Helmut (PLoS ONE, 2013)
Piccolo is one of the largest cytomatrix proteins present at active zones of chemical synapses, where it is suggested to play a role in recruiting and integrating molecules relevant for both synaptic vesicle exo- and endocytosis. Here we examined the retina of a Piccolo-mutant mouse with a targeted deletion of exon 14 in the Pclo gene. Piccolo deficiency resulted in its profound loss at conventional chemical amacrine cell synapses but retinal ribbon synapses were structurally and functionally unaffected. This led to the identification of a shorter, ribbon-specific Piccolo variant, Piccolino, present in retinal photoreceptor cells, bipolar cells, as well as in inner hair cells of the inner ear. By RT-PCR analysis and the generation of a Piccolino-specific antibody we show that non-splicing of intron 5/6 leads to premature translation termination and generation of the C-terminally truncated protein specifically expressed at active zones of ribbon synapse containing cell types. With in situ proximity ligation assays we provide evidence that this truncation leads to the absence of interaction sites for Bassoon, Munc13, and presumably also ELKS/CAST, RIM2, and the L-type Ca(2) (+) channel which exist in the full-length Piccolo at active zones of conventional chemical synapses. The putative lack of interactions with proteins of the active zone suggests a function of Piccolino at ribbon synapses of sensory neurons different from Piccolo's function at conventional chemical synapses.
EVALuna2:21139